2012
DOI: 10.1055/s-0032-1310063
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized study on the benefits of a new small-caliber colonoscope

Abstract: Use of the small-caliber colonoscope reduced pain in female patients, but offered no advantage over standard colonoscopy in male patients. The performance of the small-caliber colonoscope was equivalent to that of the standard colonoscope in terms of cecal intubation rate and time to cecum, regardless of the sex of the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 27 publications
2
49
1
Order By: Relevance
“…Therefore, we should emphasize that only with respect to easing of UC patient discomfort and pain, was the performance of the PCF‐PQ260 type significantly better than the PCF‐Q260A conventional colonoscope type. Our findings are supported by earlier studies, which reported less patient discomfort, but without the advantage in performance for ultrathin flexible colonoscopes over a standard colonoscope . However, to our knowledge, this is the first prospective study that has evaluated an ultrathin flexible scope for colonoscopy in UC patients.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Therefore, we should emphasize that only with respect to easing of UC patient discomfort and pain, was the performance of the PCF‐PQ260 type significantly better than the PCF‐Q260A conventional colonoscope type. Our findings are supported by earlier studies, which reported less patient discomfort, but without the advantage in performance for ultrathin flexible colonoscopes over a standard colonoscope . However, to our knowledge, this is the first prospective study that has evaluated an ultrathin flexible scope for colonoscopy in UC patients.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings are supported by earlier studies, which reported less patient discomfort, but without the advantage in performance for ultrathin flexible colonoscopes over a standard colonoscope. 15,18,19 However, to our knowledge, this is the first prospective study that has evaluated an ultrathin flexible scope for colonoscopy in UC patients. The main factor for the advantage of the new scope in reducing patient discomfort might be attributed to the small caliber of this design.…”
Section: N the Ultrathin Flexible-scope Group Patients'mentioning
confidence: 99%
See 2 more Smart Citations
“…The debate over quality indicators of colonoscopic examination included operator-dependent elements (such as the experience of the clinician and technical competence) as well as technical elements such as diameter of the instrument (for example ultrathin endoscopes), variable stiffness, and optical resolution [18][19][20].…”
Section: Introductionmentioning
confidence: 99%